Effect of oral contraceptives on visual evoked potentials in premenopausal females - singh Rajpoot, Raveendra; Tandon, Stuti; Kumar, Pradeep; Verma, Dileep (International Journal of Medical Research and Review, 2015)
Introduction: The sex hormones are not only restricted to the influence the reproductive organs and processes in the female body, but also have great effect on the functioning of the nervous system. Evoked potentials are one of the many electrophysiological parameters, used to assess the neuronal functioning. The aim of this prospective study was to analyze the effects of oral contraceptive pills on the visual evoked potentials in premenopausal females. Methods: The VEP was measured in 76 females during follicular and luteal phases of their menstrual cycle, and latencies of the three waveforms N70, P100 and N135 were measured. All the subjects were prescribed oral contraceptive pills containing 0.03 mg estradiol and 0.15 levonorgestrel. The VEP latencies were measured again after 4 months of oral contraceptive intake. Result: The result showed an increase in all the three latencies of VEP waveforms due to oral contraceptive intake. Although the increase in latencies were not significant (P>0.05). Conclusion: Hence it was concluded that VEP seems to be influenced by the female steroid hormones during the menstrual cycle and also due to oral intake in the form of contraceptives.